2023
DOI: 10.3390/jintelligence11020028
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors for the Advancement of Teachers’ Self-Efficacy in Professional Development

Abstract: There is a shifting paradigm in gifted education from person-based approaches (i.e., identifying giftedness) to process-based approaches (i.e., transacting giftedness). This new framework is centered on enriching educational opportunities that will make the process meaningful (i.e., gifted) to everyone in a setting. However, little is known about how this renewed perspective can be applied in teacher professional development. In line with the socio-ecological models, our study aims to identify the best appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…Theoretically, it can be explained that efficacy can encourage innovation because the teacher has high confidence to carry out tasks successfully and has appropriate emotional management skills (Gkontelos et al, 2023). This follows previous research, which stated that efficacy is significant for teachers (Buri & Moè, 2020), and teacher self-efficacy can improve education quality (Hajovsky et al, 2020;Saglam et al, 2023;Wang et al, 2022).…”
Section: Discussionsupporting
confidence: 58%
“…Theoretically, it can be explained that efficacy can encourage innovation because the teacher has high confidence to carry out tasks successfully and has appropriate emotional management skills (Gkontelos et al, 2023). This follows previous research, which stated that efficacy is significant for teachers (Buri & Moè, 2020), and teacher self-efficacy can improve education quality (Hajovsky et al, 2020;Saglam et al, 2023;Wang et al, 2022).…”
Section: Discussionsupporting
confidence: 58%
“…However, both methods have their own problems. For example, the deletion method may skew the sample size; and the imputation method, on the other hand, might not represent the true responses (Saglam et al, 2023). Furthermore, research has demonstrated that ignoring missing data in the analysis is more robust than scoring missing items as wrong responses in many situations (Finch, 2008; Rose et al, 2010).…”
Section: Methodsmentioning
confidence: 99%